2011
DOI: 10.1016/j.jmb.2011.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Community-Wide Assessment of Protein-Interface Modeling Suggests Improvements to Design Methodology

Abstract: The CAPRI and CASP prediction experiments have demonstrated the power of community wide tests of methodology in assessing the current state of the art and spurring progress in the very challenging areas of protein docking and structure prediction. We sought to bring the power of community wide experiments to bear on a very challenging protein design problem that provides a complementary but equally fundamental test of current understanding of protein-binding thermodynamics. We have generated a number of design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 19 publications
2
117
0
Order By: Relevance
“…Detailed comparison against other docking algorithms, which goes beyond the scope of this study, should be performed for a systematic evaluation. Because ZRANK is widely used and has shown considerable success in critical assessment of predicted interactions (CAPRI) experiments (35,36), we believe our method will perform comparatively well when evaluated against other top docking algorithms. The benchmarked test dataset contained a diverse set of 44 different targets that varied in size and in secondary and tertiary structures (SI Appendix, Table S3); these difficult test cases provided an opportunity to comprehensively validate the MLRbased structure discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed comparison against other docking algorithms, which goes beyond the scope of this study, should be performed for a systematic evaluation. Because ZRANK is widely used and has shown considerable success in critical assessment of predicted interactions (CAPRI) experiments (35,36), we believe our method will perform comparatively well when evaluated against other top docking algorithms. The benchmarked test dataset contained a diverse set of 44 different targets that varied in size and in secondary and tertiary structures (SI Appendix, Table S3); these difficult test cases provided an opportunity to comprehensively validate the MLRbased structure discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…These candidates are then used as the basis for computational design, with the top designs screened experimentally (e.g., for target binding affinity or catalytic activity). This approach has the advantage of providing a large amount of data that can be used to test design protocols (22,40). Alternatively, focusing on a single scaffold allows the design to take specific features of the scaffold into account.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that it is possible to achieve atomiclevel accuracy in the de novo design of protein dimers (12, 13, 16), as well as highly symmetric nanomaterials (17-20). However, the success rate of protein interface design is rather low (21), and protein interface modeling and design remain significant challenges (22).Homodimers are the most common type of protein assembly and are well represented in the Protein Data Bank (PDB). Compared with heterodimers, homodimers have a larger surface area; fewer hydrogen bonds; higher hydrophobicity; and, typically, C2 symmetry (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fleishman et al [5] recently showed that only 2 of 88 CPD-designed variants from different protein scaffolds bound to the target molecule, influenza hemagglutinin. A community-wide assessment of this study suggested that many of the failed designs do not adopt the target fold [11]. In addition, only half express solubly [12], likely due to poor stability.…”
Section: Introductionmentioning
confidence: 87%